La Charte des droits et libertés de la personne et son impact sur les assurances - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1988)
The author examines how the Charter of Human Rights and Freedoms affects insurance, where insurance legislation and insurance policies are concerned. He notes that certain clauses and underwriting regulations may give rise to problems.